Establishment of a CEMP-monitoring program at Bouvetøya - Isaksen, Kjell; Bakken, Vidar; Gjertz, Ian; Mehlum, Fridtjof (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [9 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Preliminary results from CEMP monitoring of Antarctic fur seals, chinstrap penguins and macaroni penguins at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg J G; Dyer, Bruce M; Næstvold, Alf; Mehlum, Fridtjof; Gjertz, Ian; Bakken, Vidar; Huyser, Onno (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [26 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Antarctic waste management handbook - Kankaanpää, Paula; Njåstad, Birgit; Eriksson, Cecilia (Norwegian Polar Institute, 1997)
Keywords: Antarktis; avfallshåndtering; forskningsstasjoner; miljø

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Publisher: SAGE Publications Inc
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

Establishment of Troll, a new station facility for summer operations: initial environmental evaluation - Polarinstitutt, Norsk (Norsk Polarinstitutt, 1989)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Dronning Maud Land; Norge; forskningsstasjoner; miljøspørsmål; polarforskning

Upper Air Temperatures over an Antarctic Station: A preliminary note by - Schumacher, Nils Jørgen (Tellus, 1955)
Publisher: Taylor & Francis
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Maudheim : to år i Antarktis : den norsk-britisk-svenske vitenskapelige ekspedisjon til Antarktis 1949-1952 - Giæver, John (Gyldendal, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser